Failure Modes Behavior of Different Strengthening Types of RC Slabs Subjected to Low-Velocity Impact Loading: A Review - Al-Dalaien R.N.; Syamsir A.; Abu Bakar M.S.; Usman F.; Abdullah M.J. (MDPI, 2024)
Concrete is brittle